Ewangelizacyjny charakter dziennikarstwa w nauczaniu Benedykta XVI - Guzek, Damian (Śląskie Studia Historyczno-Teologiczne, 2010)
In the reflection on the social communication Benedict XVI emphasizes the specific nature of work of media professionals. Although the Pope does not speak directly about the journalists, he writes about missionary character of their profession. In his opinion, the missionary journalism is realized in the service for providing information and shaping the public conscience. Benedict defines this type of journalism as a kind of broking. Moreover he opposes it with the journalism focused on creating the reality. Pope concentrates on Catholic journalism, given the conditions of their practice: appropriate technical preparation and adequate Christian formation. He shows the importance of Catholic journalists in the life of the Church and the particular responsibility of journalists in general, resulting from obligations to society.